Voluntary payments, privacy and social pressure on the Internet: A natural field experiment - Tobias Regner; Gerhard Riener (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
The emergence of Pay-What-You-Want (PWYW) business models as a successful alternative to conventional uniform pricing brings up new questions related to the task of pricing. We investigate the eect of a reduction of privacy on consumers' purchase decisions (whether to buy, and if so how much to pay) in a natural experiment at an online music store with PWYW-like pricing. Our study extends the empirical evidence of the reduced anonymity eect, previously established for donation or public goods contexts, to a consumption environment. We nd that revealing the name of the customer led to slightly higher payments, while it drastically reduced the number of customers purchasing. Overall, the regime led to a revenue loss of 15%. The experiment suggests that even low levels of social pressure without face to face interaction on customers leads to a reduction of welfare.
Keywords: D03; D49; H41; L82; L86; P14; 330; digital content; Internet; natural experiment; privacy; public goods; PWYW; social pressure; voluntary contributions; voluntary payments